Factors causing challenges in learning listening skills faced by first-year non-English major students at Hanoi University of Industry - Nguyễn, Thị Minh Hạnh (ĐHNN, 2017)
The role of Listening in language Learning and Teaching. Previous studies in listening problems faced by language learners. The context of Hanoi University of Industry. The English program for non-English major students at HaUI. The types and requirements of listening comprehension activities for non-English major students at HaUI. Recommendations.